Monacolin K affects lipid metabolism through SIRT1/AMPK pathway in HepG2 cells - Huang, Chia-Hsin; Shiu, Shin-Mau; Wu, Min-Tze; Chen, Wei-Lu; Wang, Shyang-Guang; Lee, Horng-Mo (Archives of pharmacal research, 2013)
Monacolin K is the secondary metabolite isolated from Monascus spp. It is the natural form of lovastatin, which is clinically used to reduce the synthesis of cholesterol by inhibiting 3-hydroxy-3-methylglutaryl coenzyme A reductase. In the present study, monacolin K increased protein expression of SIRT1 and phosphorylation level of AMP-activated protein kinase (AMPK) in HepG2 cells. Through activation of SIRT1/AMPK pathway, monacolin K increased phosphorylation of acetyl CoA carboxylase and caused nuclear translocation of forkhead box O1. The western blotting results showed that monacolin K increased expression of adipose triglyceride lipase but decreased abundances of fatty acid synthase (FAS) and sterol regulatory element-binding protein 1 (SREBP1). Monacolin K also decreased the intracellular accumulation of lipids as demonstrated by Oil Red O staining. In addition, the immunostaining showed that monacolin K prevented the nuclear translocation of SREBP1, indicating the association with down-regulation of FAS. All the demonstrated effects of monacolin K were counteracted by nicotinamide or compound C, the inhibitors of SIRT1 or AMPK. In summary, monacolin K reduces the lipid content through SIRT1/AMPK pathway in HepG2 cells, which promotes catabolism and inhibits anabolism of lipid.